Maximum-revenue tariff under Bertrand duopoly with unknown costs - Ferreira, Fernanda A. (2014)
This paper considers an international trade under Bertrand model with differentiated products and with unknown production costs. The home government imposes a speciﬁc import tariff per unit of imports from the foreign ﬁrm. We prove that this tariff is decreasing in the expected production costs of the foreign ﬁrm and increasing in the production costs of the home ﬁrm. Furthermore, it is increasing in the degree of product substitutability. We also show that an increase in the tariff results in both ﬁrms increasing their prices, an increase in both expected sales and expected proﬁts for the home ﬁrm, and a decrease in both expected sales and expected proﬁts for the foreign ﬁrm.